Images of inequality in Chile: The impact of economic and political factors - Segovia, Carolina; Instituto de Investigación en Ciencias Sociales (ICSO) (Pontificia Universidad Javeriana, 2016)
How unequal is Chilean society perceived to be by citizens? Has this image change over the last few years? What explains the levels of inequality perceived? Using data from public opinion surveys we consider these questions. Results show that Chileans believe they live in an unequal society, that those perceptions have remained stable between 2000 and 2013, with a small improvement by 2013, and that those perceptions can be explained by economic –and not political- factors.